2014
DOI: 10.1128/iai.01443-13
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Membrane Vesicles Stimulate Innate Pro- and Anti-Inflammatory Responses and Induce Apoptosis in Jurkat T Cells

Abstract: Persistent Helicobacter pylori infection induces chronic inflammation in the human gastric mucosa, which is associated with development of peptic ulceration, gastric atrophy, and gastric adenocarcinoma. It has been postulated that secretion of immunomodulatory molecules by H. pylori facilitates bacterial persistence, and membrane vesicles (MV), which have the potential to cross the gastric epithelial barrier, may mediate delivery of these molecules to host immune cells. However, bacterial MV effects on human i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 48 publications
0
62
0
7
Order By: Relevance
“…For example, H. pylori OMVs suppress T cell responses by inducing apoptosis through a pathway that involves caspase 3 and caspase 7 (REF. 44). The authors demonstrated that the VacA toxin associated with H. pylori OMVs 12,67,90 enhanced, but was not essential for, the induction of apoptosis in T cells from a Jurkat cell line 44 .…”
Section: Suppression Of T Cellsmentioning
confidence: 93%
See 3 more Smart Citations
“…For example, H. pylori OMVs suppress T cell responses by inducing apoptosis through a pathway that involves caspase 3 and caspase 7 (REF. 44). The authors demonstrated that the VacA toxin associated with H. pylori OMVs 12,67,90 enhanced, but was not essential for, the induction of apoptosis in T cells from a Jurkat cell line 44 .…”
Section: Suppression Of T Cellsmentioning
confidence: 93%
“…44). The authors demonstrated that the VacA toxin associated with H. pylori OMVs 12,67,90 enhanced, but was not essential for, the induction of apoptosis in T cells from a Jurkat cell line 44 . Similarly, opacity-associated (Opa) proteins in N. meningitidis OMVs inhibit T cell activation and proliferation by binding to human carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) on CD4 + T cells to create a zone of immunosuppression at the site of infection 91 .…”
Section: Suppression Of T Cellsmentioning
confidence: 93%
See 2 more Smart Citations
“…vesicles (OMVs; Figure 19.3), a mechanism exploited by several Gram-negative bacteria for virulence factor delivery to host cells [37][38][39]. OMVs thus may represent an important vehicle in delivering VacA and other H. pylori antigens to either epithelial or nonepithelial gastric cells, where they exert their pathogenic actions [39][40][41][42]. Moreover, surface-associated VacA can be delivered to host gastric cells through a contact-dependent mechanism [36].…”
Section: The Vaca Gene and Its Productmentioning
confidence: 99%